2009
DOI: 10.1002/anie.200900381
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Ammonia from an Iron Nitrido Complex

Abstract: Radical ideas: Reaction of the iron(IV) nitrido complex [PhB(MesIm)(3)Fe[triple chemical bond]N] (see picture, Mes=2,4,6-Me(3)C(6)H(2)) with TEMPO-H (1-hydroxy-2,2,6,6-tetramethylpiperidine) results in high yields of ammonia and quantitative formation of [PhB(MesIm)(3)Fe(tempo)]. The mechanism likely involves hydrogen-atom transfer from TEMPO-H to the nitrido complex. Similar reaction with the triphenylmethyl radical yields [PhB(MesIm)(3)Fe[triple chemical bond]N--CPh(3)].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
177
2
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(187 citation statements)
references
References 38 publications
5
177
2
2
Order By: Relevance
“…The sodium salt of TEMPO was prepared and isolated according to the literature. 9 It was subsequently treated with triethylamine hydrochloride, producing 1 in approximately 54% yield.…”
Section: Resultsmentioning
confidence: 99%
“…The sodium salt of TEMPO was prepared and isolated according to the literature. 9 It was subsequently treated with triethylamine hydrochloride, producing 1 in approximately 54% yield.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, Smith and coworkers have prepared a range of novel transition metal nitride complexes [102], some of which may represent key intermediates in the catalytic cycle of the nitrogenase enzyme. Significantly, the iron (IV) nitrido complex {PhB(MesIm) 3 }FeN releases ammonia upon reaction with a hydrogen-atom donor [103]. Subsequently, the same researchers isolated and structurally characterized the remarkable cationic iron(V) nitrido complex [{PhB(…”
Section: Tris(carbene)boratesmentioning
confidence: 99%
“…Recent reports evidenced the potential of isolated and putative nitrido complexes in intramolecular C-H [11] and dihydrogen [7,8] activation. Further prominent reactions include an hydrogen atom abstraction, [12] the dimerization to dinitrogen complexes, [13] nitrogen transfer, [14,15] and the reactions with the nucleophiles Me 3 NO [8,10] and Ph 3 P. [4,15] For the later reaction Smith et al have recently shown, that both, electron donation to and from the nitrido nitrogen atom take place in the transition state. [16] Recently, we have shown that square-planar iridium complexes with a terminal nitrido unit also react with silanes under insertion of the nitrido nitrogen atom into the Si-H bond.…”
Section: Introductionmentioning
confidence: 97%